The vapor pressure of liquid and solid water phases at conditions relevant to the atmosphere - Nachbar, Mario; Duft, Denis; Leisner, Thomas (The journal of chemical physics, 2019)
In the atmosphere, water can be present in liquid and solid phases, but the vapor phase is generally predominant. Condensed phases of water occur under a wide range of conditions, ranging from polar mesospheric clouds at the lowest atmospheric temperatures and at low pressure to the much warmer tropospheric clouds. The temperature range at which ice or water clouds are observed spans from T = 100 to 300 K with pressures ranging from about 10−3 mbar to about 1 bar. Over this wide range, water is known to form several condensed phases, which can be separated into crystalline (hexagonal and stacking disordered ice) and noncrystalline phases (liquid and supercooled liquid water, amorphous solid water). We report on the vapor pressure of these water phases with a focus on metastable amorphous solid water and stacking disordered ice in the light of recent experimental findings and discuss possible implications for the atmosphere. We present evidence that supercooled liquid water and low density amorphous solid water do not belong to the same phase and therefore, no continuous vapor pressure curve can be given.
Gesehen am 27.09.2019